Comparative Effects of Cigarette and E-Cigarette Smoking on Lactate Dehydrogenase Levels in Saliva - Noor Ibrahim Salih (American Journal of Biology and Natural Sciences, 2026)
Introduction: cigarette smoking and vaping are recognized as significant health hazards. However, the accurate effect of cigarette and vaping smoking on salivary LDH levels remain unclear. Objectives: the objective of this study is investigating the effect of cigarette smoking and vaping on oral health. Material and methods: This study was conducted between December 2023 and February 2024, and samples were collected randomly from 90 male volunteer participants. Standard techniques were employed to collect and analyse saliva samples for estimation of LDH levels. Results: Out of the 90 participants, 65 were smokers and 25 were non-smokers (control group). Cigarette smokers exhibited significantly higher levels of salivary LDH compared to both vapers and non- smokers. On the other hand, vapers showed higher salivary LDH levels than non-smokers, although their levels were lower than those observed in cigarette smokers. Conclusion: In this study both cigarette smoking and vaping significantly elevates salivary LDH levels, indicating a potential effect on oral tissues. The increase more observed among cigarette smokers compared to vapers while non-smokers showed the lowest levels. This study suggest that both forms of smoking contribute to oral tissues damage and this signifies that additional research is required to investigate the long‑term impacts of smoking and vaping on oral tissues.